Public Libraries and the Opioid Crisis, Part 2: Community-Centered Responses - Real, Brian; Bogel, Gayle (Public Library Quarterly, 2019)
Numerous articles from major national newspapers have covered the fact that as the opioid crisis has become a pervasive problem in the United States, overdoses in public libraries have become a somewhat common occurrence. Many of these discussions center on librarians being trained to use the overdose reversal drug Naloxone, and that was the primary focus of the first part of this two-part study. However, this second article discusses what libraries are doing to mitigate the impacts of the crisis and help persons from vulnerable populations before matters escalate to become emergency situations. The authors document how libraries are attempting to educate their communities about the opioid crisis, ways they have partnered with community organizations to help opioid dependent persons, and how they have addressed various facilities and security concerns for their buildings.
12 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/040-002-193-003-128, pop00139 tex.type: [object Object]
Keywords: Public libraries; dept.ils; facilities management; opioids; peer-reviewed; security; vulnerable populations